Interaction of the concentration of S2–, SO42– and microbial community by controlling nitrogen stripping during sulfate-rich wastewater treatment. Issue 1 (31st December 2022) - Shi, Ke; Jiang, Qing; Qiao, Yanlu; Xue, Jianliang; Yao, Yuehong; Niu, Liping; Sun, Shuang; Cheng, Dongle; Huang, Jin
ABSTRACT: Nitrogen stripping plays a vital role during the sulfate-rich wastewater treatment process by sulfate-reducing bacteria (SRB). However, the interaction between nitrogen stripping, sulfate reduction capacity, S 2 – concentration, and microbial community structure is rarely studied. Here, two anaerobic systems were conducted to analyze these interactions simultaneously. Results showed that the toxic products (H2 S) were stripped by nitrogen at first. Then, the increased relative abundance of fermentative bacteria accelerated the carbon sources conversion, and Desulfovibrio, Dethiosulfovibrio, and Sulfurospirillum facilitated the sulfate reduction after nitrogen stripping. Finally, the produced S 2− concentration was increased by 12%, and the sulfate reduction rate was increased by 9.2% compared to that without nitrogen stripping.